2013
DOI: 10.1111/jth.12172
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to APC and SHBG levels during use of a four-phasic oral contraceptive containing dienogest and estradiol valerate: a randomized controlled trial

Abstract: To cite this article: Raps M, Rosendaal F, Ballieux B, Rosing J, Thomassen S, Helmerhorst F, van Vliet H. Resistance to APC and SHBG levels during use of a four-phasic oral contraceptive containing dienogest and estradiol valerate: a randomized controlled trial. J Thromb Haemost 2013; 11: 855-61.Summary. Background: The use of combined oral contraceptives is associated with a 3-to 6-fold increased risk of venous thrombosis. This increased risk depends on the estrogen dose as well as the progestogen type of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
(69 reference statements)
2
17
0
2
Order By: Relevance
“…The relative risk of thrombosis during the use of norethisterone, levonorgestrel, and norgestimate is 2-3 with NNH: 2381-4762 [ 25 ]. Dienogest has a similar risk profile to levonorgestrel [ 38 ]. The relative risk of thrombosis during the use of desogestrel, gestodene, drospirenone, and contraceptive intravaginal rings was 4-6 with NNH: 952-1587 [ 39 ].…”
Section: Oral Contraception and The Risk Of Thrombosismentioning
confidence: 99%
“…The relative risk of thrombosis during the use of norethisterone, levonorgestrel, and norgestimate is 2-3 with NNH: 2381-4762 [ 25 ]. Dienogest has a similar risk profile to levonorgestrel [ 38 ]. The relative risk of thrombosis during the use of desogestrel, gestodene, drospirenone, and contraceptive intravaginal rings was 4-6 with NNH: 952-1587 [ 39 ].…”
Section: Oral Contraception and The Risk Of Thrombosismentioning
confidence: 99%
“…Of the other publications, one was a pooled study summarizing menstrual blood loss (MBL) data across two individual studies previously identified, and was included as appropriate 23. The other seven articles reported on outcomes that were not the focus of this review but were included, where appropriate, as supportive references 11,1921,2527. Ten other pertinent articles were identified from published manuscripts known to the authors or from unpublished manuscripts that were available to them and were included for discussion,14,2937 but three others were not included as the outcomes reported were not the focus of this review 3840.…”
Section: Methodsmentioning
confidence: 99%
“…Так, в проспективном когортном исследовании INAS-SCORE, включавшем 50 203 участницы, доказано, что прием КОК, содержащих ЭВ и ДНГ, ассоциирован со схожим или более низким риском развития кардиоваскулярных осложнений в сравнении с КОК, содержащими левоноргестрел, и другими оральными контрацептивами [7]. В других исследованиях также показано, что препарат, содержащий ЭВ и ДНГ, имеет аналогичное или меньшее влияние на гемостаз по сравнению с монофазными КОК, содержащими этинилэстрадиол и левоноргестрел [8,9]. Авторы отмечают, что прием ЭВ/ ДНГ сопровождался значительно меньшим увеличением уровня D-димера (37% против 88% для ЭВ/ДНГ и этинилэстрадиола/левоноргестрела соответственно) и менее выраженным ростом уровня протромбина и фибриногена [9].…”
Section: Conflict Of Interestunclassified